Combined computational analysis and cytology show limited depth osteogenic effect on bone defects in negative pressure wound therapy - Huang, Xiu-Hong; Zheng, Li-Qin; Dai, Yue-Xing; Hu, Shao-Nan; Ning, Wan-Chen; Li, Si-Min; Fan, Yue-Guang; Lin, Zi-Ling; Huang, Shao-Hong (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The treatment of bone defects remains a clinical challenge. The effect of negative pressure wound therapy (NPWT) on osteogenesis in bone defects has been recognized; however, bone marrow fluid dynamics under negative pressure (NP) remain unknown. In this study, we aimed to examine the marrow fluid mechanics within trabeculae by computational fluid dynamics (CFD) and to verify osteogenic gene expression to investigate the osteogenic depth under NP. Methods: The human femoral head is scanned using micro-CT to segment the volume of interest (VOI) trabeculae. The VOI trabeculae CFD model simulating the bone marrow cavity is developed by combining the Hypermesh and ANSYS software. The effect of trabecular anisotropy is investigated, and bone regeneration effects are simulated under NP scales of −80, −120, −160, and −200 mmHg. The working distance (WD) is proposed to describe the suction depth of the NP. Finally, gene sequence analysis, cytological experiments including bone mesenchym al stem cells (BMSCs) proliferation and osteogenic differentiation are conducted after the B MSCs are cultured under the same NP scale. Results: The pressure, shear stress on trabeculae, and marrow fluid velocity decrease exponentially with an increase in WD. The hydromechanics of fluid at any WD inside the marrow cavity can be theoretically quantified. The NP scale significantly affects the fluid properties, especially those fluid close to the NP source; however, the effect of the NP scale become marginal as WD deepens. Anisotropy of trabecular structure coupled with the anisotropic hydrodynamic behavior of bone marrow; An NP of −120 mmHg demonstrates the majority of bone formation-related genes, as well as the most effective proliferation and osteogenic differentiation of BMSCs compared to the other NP scales. Conclusion: An NP of −120 mmHg may have the optimal activated ability to promote osteogenesis, but the effective WD may be limited to a certain depth. These findings help improve the understanding of fluid mechanisms behind NPWT in treating bone defects.